The pious man and his sons - Khan, Saniyasnain (GoodwordKidz New Delhi, 2004)
This story follows a devoted father who imparts wisdom and values to his sons, guiding them on a path of righteousness. It highlights the role of parental guidance in shaping the moral character of future generations.